A pipeline of tweets: environmental movements' use of Twitter in response to the Keystone XL pipeline. Issue 2 (3rd March 2016) - Hodges, Heather E.; Stocking, Galen
ABSTRACT: Social movements often amalgamate otherwise diffuse public political interests. In recent years, social media use has allowed both groups and individuals to engage with political issues both online and offline. How do organizations use Twitter to mobilize networked publics? To what extent do groups promote both 'connective action' online and traditional activism offline? How do their strategies differ according to whether they seek to promote or combat the status quo ? And how do they balance encouraging and reinforcing individualized expression through group messaging? The ways pro-Keystone XL pipeline and anti-Keystone XL groups differed in their Keystone-related action on Twitter from January 2010 until October 2014 are analyzed. Boolean searching and Natural Language processing are used to analyze more than three million tweets. The results demonstrate that the frames within Twitter conversations have significant implications for how communities understand, develop, and mobilize around environmental issues.